Single-photon source with adjustable linear SOP - Almeida, Álvaro J. (2012)
In this work we generate and detect single photons in optical fibers using the stimulated four-wave mixing (FWM)process. The results show an accurate generation of single photons at four different linear states of polarization (SOPs), with angles 0, 45, 90 and -45 degrees.